Pengaruh Lokasi, Promosi, dan Harga Terhadap Kepuasan Konsumen Wisata Alam Selo Tirto Giri (SETIGI) - Ashef Aniqurroziqi; bambang setiyo pambudi (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
Tourism is one sector that is considered to have an important role in the development of a country and region. This research was conducted to determine the effect of location, promotion, and price on customer satisfaction of Tirto Segiri nature tourism. The independent variables studied were location (X1), promotion (X2), and price (X3), while the dependent variable was customer satisfaction (Y). The research approach used is quantitative with an explanatory method. The population in this study were all visitors to Setigi nature tourism from 2019 to 2020. The results showed that there was a positive effect of the location variable on the customer satisfaction variable, there was a positive influence of the promotion variable on the customer satisfaction variable, there was a positive effect of the price variable on the customer satisfaction variable, and there is a joint positive effect of location, promotion, and price variables on customer satisfaction variables.